A method for control proteolytic degradation of recombinant proteins. - Tey, Beng Ti; Tan, Weng Siang; Chong, Fui Chin (2010)

(untitled)
The present invention provides a method to enhance the recovery of recombinant N protein of Nipah virus produced in Escherichia coli, in which by identifying and inhibiting the specific proteases in the cell lysate are achieved by an integrated use of a bioinformatics tool and a protease inhibition experimental setup.